2006
DOI: 10.1016/j.bbabio.2006.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Production of reactive oxygen species in mitochondria of HeLa cells under oxidative stress

Abstract: Mitochondria can be a source of reactive oxygen species (ROS) and a target of oxidative damage during oxidative stress. In this connection, the effect of photodynamic treatment (PDT) with Mitotracker Red (MR) as a mitochondria-targeted photosensitizer has been studied in HeLa cells. It is shown that MR produces both singlet oxygen and superoxide anion upon photoactivation and causes photoinactivation of gramicidin channels in a model system (planar lipid bilayer). Mitochondria-targeted antioxidant (MitoQ) inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 28 publications
5
62
0
1
Order By: Relevance
“…This could reflect the diffusion of ROS from mitochondria to other compartments or ROS-induced ROS generation. 27,28 To delineate the role of the mitochondrial electron transport chain in HNE-induced ROS generation and TF decryption, cells were pretreated with specific inhibitors of electron transport chain complexes. As shown in Figure 1B, the inhibitors of complex I, II, and IV (ie, rotenone, THF, and sodium azide, respectively) did not inhibit HNE-induced ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…This could reflect the diffusion of ROS from mitochondria to other compartments or ROS-induced ROS generation. 27,28 To delineate the role of the mitochondrial electron transport chain in HNE-induced ROS generation and TF decryption, cells were pretreated with specific inhibitors of electron transport chain complexes. As shown in Figure 1B, the inhibitors of complex I, II, and IV (ie, rotenone, THF, and sodium azide, respectively) did not inhibit HNE-induced ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…Although our model envisions extracellular production of ROS, certain species, such as hydrogen peroxide, can diffuse through membranes and cause intracellular damage. Also, it has recently been shown that extracellular oxidative stress increases ROS production in the mitochondria of HeLa cells (Chernyak et al 2006). However, an alternative explanation for CTL-2's and SOD-3's protective effects is that there is an increase only in intracellular ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the response of the different mutant strains to H 2 O 2 mirrored their response to PHS in terms of sensitivity. Hydrogen peroxide can cause oxidative stress and cell death since it easily permeates through cellular membranes (55) and it induces the production of more ROS (41). We reasoned that ROS production/removal could be a key factor in PHSinduced cell death and explain why different strains display different responses to the drug.…”
Section: Discussionmentioning
confidence: 99%